Epidemiological pattern of contact dermatitis among urban and rural Patients attending a tertiary care center in a semi-urban area in Eastern India - Shinjini Ghosh; Sourav Kundu; Sanjay Ghosh (Wolters Kluwer Medknow Publications, 2020)
Background: There is a trend of increase in number of contact dermatitis cases. Studies on the prevalence and epidemiological pattern of allergic skin disorders in Indian scenario are not much available. The present study was designed to assess the epidemiological pattern of contact dermatitis in rural and urban areas in a peripheral district in eastern India. Aims and Objectives: This study was undertaken to find the prevalence of contact dermatitis and to assess the epidemiological pattern of contact dermatitis both in rural and urban community. Materials and Methods: The study was conducted in a medical college located at a semi-urban area in eastern India with written informed consent obtained from each participant. This hospital-based cross-sectional study was done from May 2017 to April 2018. Study population consisted of patients attending the dermatology OPD and having lesions clinically suggestive of contact dermatitis and there were 268 such patients. Patients attending the OPD were divided into urban and rural as per their address. Data analysis was done using suitable, standard, and appropriate statistical methods. Results: The prevalence of contact dermatitis was 4.38% among the dermatology OPD attendees. Urban prevalence was statistically significantly (P < 0.05) higher than rural prevalence. Contact dermatitis was common in the age group of 41-50 years. In urban areas, females were more affected than those in rural areas. Occupationally, the difference between urban and rural patients of contact dermatitis was statistically significant (P < 0.05). Cosmetic history in the urban group was significantly more (P < 0.05). Conclusions: Contact dermatitis prevalence and patient profile in certain factors showed a statistically significant difference between urban and rural patients.